Literasi penulisan Bahasa Inggeris dalam kalangan pelajar luar bandar: Implikasi terhadap pengajaran dan pembelajaran - Siti Hamin Stapa,; Nadzrah Abu Bakar,; Rozmel Abdul Latiff, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
The objective of this article is to investigate the level of written literacy in English among students in the rural area in Malaysia. This article is based on a research conducted at three secondary schools in the district of Kulai, Johor. For the purpose of data collection, a writing test was administered to Form Two students at the three secondary schools. The research findings reveal that the level of written literacy among these students ranges from weak to satisfactory. This article closes with a discussion on the implications of these research findings on the teaching and learning of writing in English especially in the rural area